Performance Analysis Of Marketing and Customer Service Division Using The 5W1H Method and Fishbone Diagram At PT XYZ - Muhammad Alfafa Rizky; Sumiati Sumiati (International Journal of Mechanical, Industrial and Control Systems Engineering, 2024)
In an era of increasingly fierce competition in the energy sector, companies are required to not only meet customer needs, but also to improve service quality and customer satisfaction in a sustainable manner. This study aims to analyze and improve the performance of the Marketing and Customer Service Division at PT XYZ by applying the 5W1H method and the Fishbone Diagram. The study identified a number of factors that contributed to the division's low performance, including a lack of adequate training and decreased work motivation. Through in-depth analysis, this study provides strategic recommendations to improve the quality of training, the development of an integrated information system, and the establishment of clear service standards. The implementation of these recommendations is expected to improve productivity, service quality, and customer satisfaction, as well as strengthen the company's position in a competitive market.